Discourse constructions of youth identities - Androutsopoulos, Jannis K.; Georgakopoulou, Alexandra (Amsterdam ; Philadelphia : J. Benjamins, 2003)
This volume sets out to foreground the issues of youth identity in the context of current sociolinguistic and discourse research on identity construction. Based on detailed empirical analyses, the twelve chapters offer examinations of how youth identities from late childhood up to early twenties are locally constructed in text and talk. The settings and types of social organization investigated range from private letters to graffiti, from peer group talk to video clips, from schoolyard to prison. Comparably, a wide range of languages is brought into focus, including Danish, German, Greek, Japa.
Discourse Constructions of Youth Identities; Editorial page; Title page; LCC page; Contributors; Table of contents; Discourse constructions of youth identities: Introduction; I. Peer group identities; II. Recasting literacy practices; III. Representations and positionings; Index; The PRAGMATICS AND BEYOND NEW SERIES.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Youth -- Language; Discourse analysis; Identity (Psychology) in youth; Jeunesse -- Langage; Analyse du discours; Identité chez les jeunes; pragmatics; REFERENCE; LANGUAGE ARTS & DISCIPLINES -- Vocabulary; Discourse analysis; Identity (Psychology) in youth; Youth -- Language; Spreektaal; Identiteit; Jongeren; Electronic book